Música litúrgica a la Biblioteca de Catalunya I: Llibres de cant litúrgic manuscrits - Gudayol Torelló, Anna (Miscel·lània litúrgica catalana, 2017)
La Biblioteca de Catalunya holds a remarkable collection of liturgical music manuscripts, coming from diferent places and origins. In the centennial of its Music Department, a catalog of the manuscript music in Gregorian chant preserved in the Library has been dressed; it includes books compiled to be used in the mass and in the divin office, from the XIIth to the XIXth century. The catalog is divised in two parts: the present work, that describes manuscripts bequeathed, donated or bought by the Library, and a second one, that will describe the liturgical choir books entered in the Library during the Spanish Civil War. It is preceded by a state of the question in research and cataloging of medieval liturgical music and a brief explanation on the library collection, and followed by onomastical, toponymical and typology indexes.